1995
DOI: 10.1002/hep.1840210205
|View full text |Cite
|
Sign up to set email alerts
|

Ability of prolonged interferon treatment to suppress relapse after cessation of therapy in patients with chronic hepatitis C: A multicenter randomized controlled trial

Abstract: The aim of this study was to determine whether 12 months course of interferon alfa (IFN-alpha) therapy could improve the beneficial effect of IFN in chronic hepatitis C. Eighty-eight patients were treated with natural IFN-alpha for either 28 weeks (45 cases) or 52 weeks (43 cases). Sustained response was achieved in 15 (33.3%) of 45 cases treated for 28 weeks and in 23 (53.5%) of 43 cases treated for 52 weeks. Transient response with relapse of alanine transaminase (ALT) after completion of therapy was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…The present study as well as our previous study [13] showed that speci®c HCV genotypes are associated with the amount of HCV RNA, the severity of liver disease, and the ecacy of IFN therapy in children, as previously reported in adults [9,19,21]. Findings support the idea that patients with the HCV genotype II (Simmond Ib) [6] are less likely to respond than the HCV genotype III (Simmond 2a), and the more prolonged therapy with IFN may improve the outcome of retreatment after the failure of the initial course of IFN.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The present study as well as our previous study [13] showed that speci®c HCV genotypes are associated with the amount of HCV RNA, the severity of liver disease, and the ecacy of IFN therapy in children, as previously reported in adults [9,19,21]. Findings support the idea that patients with the HCV genotype II (Simmond Ib) [6] are less likely to respond than the HCV genotype III (Simmond 2a), and the more prolonged therapy with IFN may improve the outcome of retreatment after the failure of the initial course of IFN.…”
Section: Discussionsupporting
confidence: 74%
“…Interferon-a (IFN-a) is up to now the most promising treatment of chronic hepatitis C virus (HCV) infection, however only 10%±33% of adult patients with chronic HCV infection show a sustained complete response after treatment is completed [4,5,9,18]. The rarity of liver cirrhosis and severe chronic active hepatitis (CAH) in children led to the speculation that their response could be better than adults when treated with IFN-a for chronic HCV infection [3,7,13,16].…”
Section: Introductionmentioning
confidence: 99%
“…The virological characteristics tal IFN dose of 468 MU over 6 (28%) or 12 months most consistently predictive of a low likelihood of sus-(31%). The low sustained response rate in our study, as tained response are high levels of pretreatment viremia compared to others [Jouët et al, 1994;Kasahara et al, and infection with HCV type 1, especially 1b [Kanai et 1995], might be due more to the unfavorable features al., 1992; Chemello et al, 1994;Tsubota et al, 1994; of patients than to the actual schedule of treatment. Booth et al, 1993].…”
Section: Sustainedmentioning
confidence: 71%
“…Currently, as shown in many studies, interferon (IFN) is the only drug that induces viral clearance and marked biochemical and histological improvement in patients with chronic hepatitis C. [1][2][3][4][5][6][7][8][9][10][11][12] In these many studies, hepatitis C virus (HCV)-RNA clearance rates were reported to be about 30%-40% in patients treated with a course of IFN of less than 6 months. However, with respect to IFN treatment for chronic hepatitis C, normalization of alanine aminotransferase (ALT) as well as clearance of HCV-RNA after IFN therapy is important.…”
Section: Introductionmentioning
confidence: 99%